2018
DOI: 10.1159/000492431
|View full text |Cite
|
Sign up to set email alerts
|

Airway-Centered Pleuroparenchymal Fibroelastosis Associated with Non-Necrotizing Granulomas: A Rare New Entity

Abstract: Pleuroparenchymal fibroelastosis is a rare form of upper-lobe-dominant progressive pulmonary fibrosis characterized histologically by visceral pleural thickening with collagenous fibrosis, subpleural elastosis, and intra-alveolar collagenous fibrosis. It was first described 25 years ago by Amitani et al. This report firstly describes a new variant or rare phenotype of PPFE with airway involvement, minimal pleuroparenchymal connections, and non-necrotizing granulomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Karam et al, in 1982 reported a case of a patient with GCA without specific interstitial lung involvement and no PPFE evidence [23] while more recently Konoshi et al described a clinical case without PPFE evidence at HRCT [24]. The lung involvement in GCA is rare and interstitial lung diseases (ILD) are usually reported as an uncommon clinical manifestation of GCA [25]. Our patient is probably the first case presenting PPFE associated with GCA and we wonder if this is a real associative disease or a coincidence, perhaps secondary to drug effects.…”
Section: Discussionmentioning
confidence: 99%
“…Karam et al, in 1982 reported a case of a patient with GCA without specific interstitial lung involvement and no PPFE evidence [23] while more recently Konoshi et al described a clinical case without PPFE evidence at HRCT [24]. The lung involvement in GCA is rare and interstitial lung diseases (ILD) are usually reported as an uncommon clinical manifestation of GCA [25]. Our patient is probably the first case presenting PPFE associated with GCA and we wonder if this is a real associative disease or a coincidence, perhaps secondary to drug effects.…”
Section: Discussionmentioning
confidence: 99%
“…[3–5] First described 25 years ago, [6] PPFE is now considered a distinct entity that may be familial, idiopathic, or associated with pathological conditions such as hypersensitivity pneumonitis (HP), pneumoconiosis, bone marrow or lung transplant, drug-induced lung toxicity, and connective tissue diseases. [6–12] PPFE may coexist with different radiological and histological ILD patterns: usual interstitial pneumonia (UIP), non-specific interstitial pneumonia (NSIP), granulomatous lung diseases, and chronic hypersensitivity pneumonitis (HP). [13] Radiological PPFE has also been reported in patients with recurrent respiratory infections, which is in line with the theory that repeated inflammatory stimuli may trigger the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Airway-centered fibroelastosis has recently been described as a unique and distinct entity in five non-smoking middleaged women with evidence of prominent airway-centered elastosis in their lung samples (9). Following the publication of this report, a few cases with similar characteristics have been reported (10)(11)(12). The clinical course of previously reported cases indicates that patients with airway-centered fibroelastosis have progressive disease and a poor prognosis.…”
Section: Introductionmentioning
confidence: 72%